Genetic diversity and relationship of D-loop sequences among animals in Cervidae and their application for preliminary screening of sambar deer origin in unknown meat - Pitchaya Munsuwan; Chavin Chaisongkram; Wibhu Kutanan; Khemika Lomthaisong (Agriculture and Natural Resources, 2021)
The D-loop sequences of seven Cervidae species—sambar deer (Rusa unicolor), rusa deer (Rusa timorensis), sika deer (Cervus nippon), Eld’s deer (Rucervus eldii), muntjac (Muntiacus muntjak), chital deer (Axis axis) and hog deer (Axis porcinus)—were analyzed for their genetic diversity and relationships. D-loop amplifications of DNA extracted from blood samples (five specimens/species) showed product sizing in the range 1,000–1,100 bp. These amplicons were sequenced and analyzed for genetic diversity within species. Genetic diversity was highest in hog deer (haplotype diversity (h) = 0.9, nucleotide diversity (π) = 0.02796) and lowest in muntjac (h = 0.4, = 0.00879). The phylogenetic relationship of the D-loop sequence (701 bp) was analyzed. Most samples were in the same subclade as their original species, indicating the possibility of using the D-loop as target DNA for cervid species identification. This was tested by examining three meat samples of unknown species origin. The D-loop amplification of the unknown meats showed two different sizes of amplicons of 1,000 bp (Unknown1) and 1,500 bp (Unknown2, Unknown3). These D-loop sequences (281 bp) were compared with those of cervid references. The two unknown meats presenting 1,500 bp amplicons were an outgroup and one was in the same subclade as muntjac. The results were confirmed using BLAST analysis from which the two outgroup samples were similar to domestic pig (99.74%) and dog (97.82%), respectively, while the third sample had greatest similarity to muntjac (97.81%). The method presented here could be used with meat samples for preliminary screening to prove whether or not the sample was from sambar deer (a protected species in Thailand), which could be observed by either the size of the amplicons or the phylogenetic relationship of the D-loop sequence.